2016
DOI: 10.1002/rsa.20667
|View full text |Cite
|
Sign up to set email alerts
|

A note on the random greedy independent set algorithm

Abstract: Let r be a fixed constant and let scriptH be an r‐uniform, D‐regular hypergraph on N vertices. Assume further that D>Nϵ for some ϵ>0. Consider the random greedy algorithm for forming an independent set in scriptH. An independent set is chosen at random by iteratively choosing vertices at random to be in the independent set. At each step we chose a vertex uniformly at random from the collection of vertices that could be added to the independent set (i.e. the collection of vertices v with the property that v is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(80 citation statements)
references
References 34 publications
3
77
0
Order By: Relevance
“…We remark that in [40] the authors stated that in a private communication, Jacques Verstraëte suggested that a lower bound on ex r (n, B t ), which is exactly the same with Proposition 8, can also be proved by using the method of [8,7] (which is rather involved). Nevertheless, since [40] stated this result (as well as Proposition 13 below) without a proof, we present it here as an easy consequence of Theorem 3.…”
Section: R-graphs With No Short Berge Cyclesmentioning
confidence: 59%
“…We remark that in [40] the authors stated that in a private communication, Jacques Verstraëte suggested that a lower bound on ex r (n, B t ), which is exactly the same with Proposition 8, can also be proved by using the method of [8,7] (which is rather involved). Nevertheless, since [40] stated this result (as well as Proposition 13 below) without a proof, we present it here as an easy consequence of Theorem 3.…”
Section: R-graphs With No Short Berge Cyclesmentioning
confidence: 59%
“…holds for all n. This was first proved by Bohman and Keevash [11] and later generalized to hypergraphs of higher uniformity by Bennett and Bohman [10].…”
Section: Proofs Of Theorems 2 Andmentioning
confidence: 76%
“…For a fixed (hyper-)graph H, the H-free process has been extensively studied, in particular if H is 'strictly 2-balanced' (see e.g. [2,4,21,27,32,33]). A particular challenge arising in the analysis of the current process is that each individual Erdős-configuration in H has a significant influence on the trajectory of the process.…”
Section: Theorem 13 ([24]mentioning
confidence: 99%
“…The following is an immediate consequence of Proposition 5.9. For distinct triples T 1 , T 2 , we let X T 1 ,T 2 (i) be the set of all pairs S 1 = S 2 , not both diamonds, such that for each ℓ ∈ [2], S ℓ ∈ X T ℓ ,j ℓ ,j ℓ −4 (i) with 4 ≤ j ℓ ≤ j max , and such that (…”
Section: Counting Double Configurationsmentioning
confidence: 99%